Deliberating the Constitutional Supremacy from the Legal and Judicial Perspective with Special Reference to the Palestinian Situation - Hamad, Ahmed M. A.; Mohd Anuar, Haslinda (Universitas Sebelas Maret, 2022)
Constitutional supremacy, the supremacy of the basic law, is considered as the system of government in which the freedom of the legislature of parliamentary supremacy relinquishes to the requirements of a constitution. This article examines the constitutional supremacy or the supremacy of the basic law from the legal and judicial perspective with particular reference to the Palestinian Situation. In addition, constitutions differentiate according to whether they are codified or not into written constitutions and unwritten constitutions. Besides, constitutions differ in terms of how they are amended into flexible and rigid constitutions. Palestinian Basic Law of 2003 is not explicitly provided with any legal provision or article in the Basic Law about the principle of constitutional supremacy or the supremacy of the basic law. However, some elements and legal provisions or articles could make the Basic Law supreme. Moreover, constitutional oversight to secure the supremacy of the Basic Law of 2003. To achieve the objectives of the article, doctrinal legal research methodology using a qualitative approach was adopted. This article concluded that the Palestinian Basic Law of 2003 has adopted the principle of the supremacy of the Basic Law of 2003 over ordinary laws and subsidiaries within the state of Palestine. This is considered an application of the principle of the rule of law stipulated in the Basic Law of 2003. The article emphasises the need to explicitly mention the principle of constitutional supremacy or the supremacy of the basic law by amending the Basic Law of 2003